The taxonomic status of an introduced freshwater goby of the genus Rhinogobius to Iran (Teleostei: Gobiidae). Issue 1 (2nd January 2019) - Sadeghi, Reza; Esmaeili, Hamid Reza; Zarei, Fatah; Esmaeili, Amirhossein; Abbasi, Keivan
Abstract : The taxonomic status of Iranian populations of an introduced freshwater goby of the genus Rhinogobius is analysed. The populations examined here had previously been considered as Rhinogobius similis or R. cheni . Comparison of new material with a recent re-description of R. similis reviewing the morphological characters available in the literature, and recent morphogenetic studies of material collected in Iran, revealed that the introduced goby should be designated as R. lindbergi . New records show that the distribution of this species extends to the Tigris River system (Persian Gulf basin) far outside of its native range. It has been probably introduced accidentally.